2022
DOI: 10.1001/jamaoto.2022.0925
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Cone-Beam Computed Tomography Pediatric Airway Measurements After Adenotonsillectomy in Patients With OSA

Abstract: IMPORTANCEEarly intervention using cone-beam computed tomography (CBCT) and adenotonsillectomy for children with obstructive sleep apnea (OSA) may prevent impaired growth, adverse cardiovascular consequences, learning deficits, and poor quality of life.OBJECTIVE To assess changes in CBCT airway measurements and polysomnography (PSG) parameters that occur after adenotonsillectomy in children with OSA and to determine whether CBCT changes are correlated with apnea-hypopnea index (AHI) reduction. DESIGN, SETTING,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…The CBCT was obtained using i-CAT ® imaging system (Imaging Sciences International, LLC, 1910 N Penn Road, Hatfield, PA 19440) at National XX University Hospital. 14,18 Before entering the CBCT chamber, children sit upright holding their heads still onto the chin supporter wearing lead suits with thyroid shields. The upper airway protocol applied was 120 kV, 5 mA, 0.25-mm voxel size, for a scanning time of 20 seconds.…”
Section: Cone-beam Computed Tomography (Cbct)mentioning
confidence: 99%
See 1 more Smart Citation
“…The CBCT was obtained using i-CAT ® imaging system (Imaging Sciences International, LLC, 1910 N Penn Road, Hatfield, PA 19440) at National XX University Hospital. 14,18 Before entering the CBCT chamber, children sit upright holding their heads still onto the chin supporter wearing lead suits with thyroid shields. The upper airway protocol applied was 120 kV, 5 mA, 0.25-mm voxel size, for a scanning time of 20 seconds.…”
Section: Cone-beam Computed Tomography (Cbct)mentioning
confidence: 99%
“…The authors thank the technical support of the Soteria Biotech in computational fluid dynamics simulation and the Staff of the Center of Sleep Disorder, National Taiwan University Hospital for their support in sleep studies. Parts of children in this study are derived from our previous study (see references [14,18]). We are grateful for the cooperation and participation of all of the children and their parents.…”
Section: Acknowledgementsmentioning
confidence: 99%
“…CBCT has several advantages over MRI in terms of time efficiency and low radiation exposure. Moreover, it can be used to assess response to treatment after the use of maxillomandibular advancement or dental appliances, and it provides a 3D view of the airway structures, which may be more useful than classic craniofacial analysis, which is only 2D 33 …”
Section: Diagnosis Of Sdb: Beyond the Ahimentioning
confidence: 99%
“…32 Cone-beam computed tomography (CBCT) is an alternative imaging approach for airway measurement. Liu et al 33 conducted a prospective study to investigate changes in CBCT parameters before and after adenotonsillectomy, as well as their association with reduction in AHI. They found that although large changes in CBCT were measured after the procedure, only the minimal airway area of the oropharynx and total airway volume were associated with AHI reduction.…”
Section: Dise and Imagingmentioning
confidence: 99%
“…In children, lymphoid tissue hyperplasia is the most common anatomical abnormality associated with OSA, and adenotonsillectomy is an effective treatment for reducing upper airway collapse. 5 Some patients show incomplete or worsening resolution after surgical intervention. 6 , 7 Upper airway volume in children undergoes dynamic changes due to the inter-reactions of maxillofacial growth, fat deposition, lymphoid tissue hyperplasia, and respiratory patterns.…”
Section: Introductionmentioning
confidence: 99%